Job Satisfaction and performance of elementary school teachers - Agustinus Kia Wolomasi; Sandra Ingried Asaloei; Basilius Redan Werang (International Journal of Evaluation and Research in Education (IJERE), 2019)
Given the high demands of contemporary community on the development of the youth, teachers’ job performance both inside and outside the classroom is of crucial for all partake parties, including school leaders, parents, education policymakers, and community at large. This study was meant to describe job satisfaction of elementary school teachers of Boven Digoel district, Papua, and how it predicts their job performance. To do so, we applied a survey research. Two survey questionnaire were self-administered to 352 teacher-respondent which were incidentally drawn from amongst 412 elementary school teachers of Boven Digoel district, Papua. Derived data were examined statistically using simple linear regression analysis method by utilizing Statistical Package for the Social Sciences (SPSS) version 21. Result of data analysis showed that job performance of elementary school teachers of Boben Digoel district is significant positively predicted by their job satisfaction. Finding of this study may be imperative for the school management and education administrator at the regional authority to make paramount efforts of creating valuable plans for enhancing teacher’s satisfaction in order to promote a better job performance of elementary school teachers of Boven Digoel district, Papua.